Potencial de geração e emissões em motor gerador utilizando diesel e biodiesel de canola e soja - Orben, Jean Michel Chaves (2024)
This study compared the combustion efficiency and emissions of a generator engine fueled by different types of fuels: S10 diesel, refined canola oil biodiesel, extra virgin soybean oil biodiesel, refined soybean oil biodiesel, and extra virgin soybean oil biodiesel. Various biodiesel blends (B5, B10, B20, B40, B80, B100) were tested to assess performance and environmental impact of biodiesel use compared to S10 diesel (B0). The biodiesels were produced at the Laboratory of Technology and Sustainability (LABTES) of UNIOESTE, Cascavel campus, Paraná, while sample characterization was performed by the Poollab Laboratory in Itajaí, Santa Catarina. The tests were conducted on a 5 kVA generator engine under various loads from 1,000 to 6,000 W. Evaluated parameters included instantaneous power, emissions of carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides (NOx), and hydrocarbons (HC), using ANOVA statistical analyses and Tukey's test with a 5% significance. The results revealed that adding biodiesel to S10 diesel can significantly reduce HC and NOx emissions, with notable statistical differences starting from 5% biodiesel in the blend. This trend in emission reduction continued with increasing biodiesel concentration, without significant changes in emissions from 5% biodiesel onwards. There were no significant differences in power for the different blends or raw materials. This work also highlighted that, despite the physico-chemical similarities between the different biodiesels, small incremental differences were observed. The most distinctive feature was the ester content, indicating a superior quality of extra virgin oils compared to refined ones, although this did not translate into an increase in power.